Discussing the "decadence" of são paulo: the complex insertion of sao paulo into merchant networks of the portuguese empire (1765-1808) (2014)
As a result of a joint analysis of historiographical texts and primary sources, in this paper we intend to discuss the images of "decadence" and "poverty" regarding the capitania of São Paulo in the second half of the 18th century. In this perspective, we examine how such expressions were used as arguments to the discourse of local authorities, focusing on the demonstration of the complexity of social and economic systems in São Paulo at the time.